Reinterpreting the Indonesia’s Relations with the Middle East towards the Era of Society 5.0 - Istadiyantha, Istadiyantha (IJISH (International Journal of Islamic Studies and Humanities), 2021)
This paper aimed at opening up opportunities to look for new meanings in Indonesia's relations with Middle Eastern countries, which are no longer a binary opposition, such as good and black and white, but are searching for colors and other positive meanings. Many people interpret an entity solely on the basis of a frozen meaning, a static meaning, and seem monotonous. Deconstruction seeks to offer a new meaning through re-actualization, redefinition, and/or re-interpretation. In general, this paper discusses the "new meaning" of Indonesia's relations with the Middle East. This paper argues that to welcome Society 5.0 through Humanism, both Indonesia and the Middle East share the same opportunity to advance humanism aspects that would be applicable to that era. Humanism which is being developed must be controlled by three things: anthropocentric, echocentric and theocentric. We need human beings' intelligent role in a society that chooses and sorts super intelligent technology to share common virtues. Hopefully, in the meantime the Society 5.0 era will bring much help for the Indonesia's cooperation with the Middle Eastern countries for a better future of both.